Is 6-month GRACE risk score a useful tool to predict stroke after an acute coronary syndrome?. Issue 1 (22nd December 2014) - Álvarez-Álvarez, Belén; Raposeiras-Roubín, Sergio; Abu-Assi, Emad; Cambeiro-González, Cristina; Gestal-Romaní, Santiago; López-López, Andrea; Bouzas-Cruz, Noelia; Castiñeira-Busto, María; Saidhodjayeva, Ozoda; Redondo-Diéguez, Alfredo; Pereira López, Eva; García-Acuña, José María; et al.
Abstract : Objectives: The risk of stroke after an acute coronary syndrome (ACS) has increased. The aim of this study was to do a comparative validation of the 6-month GRACE (Global Registry of Acute Coronary Events) risk score and CH2 DS2 VASc risk score to predict the risk of post-ACS ischaemic stroke. Methods: This was a retrospective study carried out in a single centre with 4229 patients with ACS discharged between 2004 and 2010 (66.9±12.8 years, 27.9% women, 64.2% underwent percutaneous coronary intervention). The primary end point is the occurrence of an ischaemic stroke during follow-up (median 4.6 years, IQR 2.7–7.1 years). Results: 184 (4.4%) patients developed an ischaemic stroke; 153 (83.2%) had sinus rhythm and 31 (16.9%) had atrial fibrillation. Patients with stroke were older, with higher rates of hypertension, diabetes, previous stroke and previous coronary artery disease. The HR for CHA2 DS2 VASc was 1.36 (95% CI, 1.27 to 1.48, p<0.001) and for GRACE, HR was 1.02(95% CI, 1.01 to 1.03, p<0.001). Both risk scores show adequate discriminative ability (c-index 0.63±0.02 and 0.60±0.02 for CHA2 DS2 VASc and GRACE, respectively). In the reclassification method there was no difference (Net Reclassification Improvement 1.98%, p=0.69). Comparing moderate-risk/high-risk patients with low-risk patients, both risk scores showed very high negative predictive value (98.5% for CHA2 DS2 VASc, 98.1% for GRACE). The sensitivity of CHA2 DS2 VASc score was higher than the GRACE risk score (95.1% vs 87.0%), whereas specificity was lower (14.4% vs 30.2%). Conclusions: The 6-month GRACE model is a clinical risk score that facilitates the identification of individual patients who are at high risk of ischaemic stroke after ACS discharge.